Prediction of vertical gradient of gravity and its significance for volcano monitoring – example from Teide volcano - ZAHOREC, Pavol; VAJDA, Peter; PAPČO, Juraj; SAINZ-MAZA Aparicio, Sergio; PEREDA De Pablo, Jorge (Contributions to Geophysics and Geodesy, 2016)
We present a detailed calculation of the topographic contribution to the vertical gradient of gravity (VGG) based on high-resolution digital elevation model (DEM) and new developed software (Toposk) for the purpose of predicting the actual VGGs in the field. The calculations presented here were performed for the Central Volcanic Complex (CVC) of Tenerife. We aimed at identifying the most extreme VGGs within the CVC, as well as predicting the VGGs at benchmarks of the former microgravity/deformation network set up to monitor the 2004/5 unrest. We have carried out an observational campaign in June 2016 to verify the predicted VGG values, both the extreme ones and those at the benchmarks. The comparison between the predicted and the in-situ verified VGGs is presented here. We demonstrate the sensitivity of the VGG prediction to the choice of the topo-rock density, which is inherent to the volcanic areas with high variability of rock densities. We illustrate the significance of the use of actual VGG in volcano monitoring microgravimetric surveys on a couple of benchmarks of the CVC network.